ANALISIS KOMPETENSI PEDAGOGIK CALON GURU DALAM MENGELOLA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI DIGITAL: STUDI KASUS PADA KEGIATAN PRAKTIK LAPANGAN PERSEKOLAHAN (PLP) 2 DI SMA NEGERI 3 BONE - Agustino, Muh Rifki; Andi Srimularahmah; Rifqi Aidil Hamdi; Muh. Qisky Agastya; Agustang; Futriani Zainuddin; Muh. Haikal Akbar; Nur Aini; Putri, Dwi; Akmal; Andi Mandasini; Syahrul Ramadhani; Afif Ramadan; Devianti Asmasari; Miftahul Fikri; Andi Syahrani; Alfin Saptahadi; Dhisar Junia Firsta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the gap between technical and pedagogical competencies among pre-service teachers in managing interactive technology-based learning during the Field Experience Program (PLP 2). The research aimed to describe and analyze pre-service teachers' pedagogical competence across three dimensions: learning planning, implementation, and evaluation of digital technology-based learning. A qualitative case study approach was employed, with six pre-service teachers and one supervising teacher at SMA Negeri 3 Bone, South Sulawesi, as research subjects. Data were collected through direct observation, in-depth interviews, and documentation analysis, then analyzed using Miles and Huberman's interactive model. The findings reveal that pre-service teachers demonstrated high technical proficiency in operating digital platforms; however, this capability did not automatically translate into effective pedagogical integration. In the planning dimension, technology selection was predominantly habit-driven rather than aligned with learning objectives, reflecting an incomplete internalization of TPACK principles. In the implementation dimension, learning patterns remained largely teacher-centered and unidirectional, with limited interactive and collaborative engagement from students. In the evaluation dimension, the most critical weakness was identified: digital assessment tools were used only for administrative purposes, with no utilization of platform analytics for diagnostic or reflective improvement. These findings confirm that the core challenge lies not in technology access, but in the quality of pedagogical integration accompanying its use, underscoring the urgency of restructuring PLP 2 as a structured digital competency development laboratory.